Answer:
graph it
Step-by-step explanation:
For this case we must indicate an expression equivalent to:
![17 (x + 5)](https://tex.z-dn.net/?f=17%20%28x%20%2B%205%29)
By definition we have that the distributive property establishes that:
![a (b + c) = ab + ac](https://tex.z-dn.net/?f=a%20%28b%20%2B%20c%29%20%3D%20ab%20%2B%20ac)
Then, applying the property to the given expression we have:
![17 (x + 5) = 17 * x + 17 * 5 = 17x + 85](https://tex.z-dn.net/?f=17%20%28x%20%2B%205%29%20%3D%2017%20%2A%20x%20%2B%2017%20%2A%205%20%3D%2017x%20%2B%2085)
Thus, an equivalent expression is:
![17x + 85](https://tex.z-dn.net/?f=17x%20%2B%2085)
ANswer:
![17x + 85](https://tex.z-dn.net/?f=17x%20%2B%2085)
<h2>
Answer:</h2>
Using the distributive property, we can simplify the expression.
4 × 3 = 12
4 ×
= 1
4 ×
= -2
Here is the simplified expression:
![12 + c - 2d](https://tex.z-dn.net/?f=12%20%2B%20c%20-%202d)